Psychological safety in enhancing the competence of nurse educators among early career nursing faculty in Japan: A cross-sectional study - Miho Satoh; Naoko Sato; Noriko Tamura; Akiko Fujimura (Elsevier, 2024)
Background: Given the diverse roles and responsibilities expected of academic nurse educators, it is essential that they acquire relevant nursing educator competencies. Early career nursing faculty often struggle to engage in their tasks. Therefore, systematic support is crucial in developing the necessary capacities for early career nursing faculty. In organizational sociology, the positive interaction between organizational and individual resources enhances the competence of nurse educators. Psychological safety enhances organizational members' ability to cope with challenges and perform effectively. It may also foster a high sense of coherence, linked to improved job performance and competence in nursing faculty. Both psychological safety and coherence promote work engagement, further boosting nurse educator competence. Aim: This study explored the relationships between psychological safety, sense of coherence, work engagement, and competence of nurse educators among assistant professors and assistants in nursing education. Design: A cross-sectional survey design was used. Data were collected from 164 early career nursing faculty using an anonymous self-administered web-based questionnaire. The study measured the psychological safety, sense of coherence, work engagement, and competence of academic nurse educators. The mediating effects of a sense of coherence and work engagement on the relationship between psychological safety and competency were assessed using the PROCESS macro model. Bootstrapping with 5,000 re-samples was used to determine the significance of the mediating effects. Setting: The study was conducted from October 1 to December 31, 2022, at nursing universities in Japan. Results: Positive correlations were identified among psychological safety, sense of coherence, work engagement, and the competence of nurse educator. The sense of coherence and work engagement indirectly mediated the relationship between psychological safety and the competence of nurse educator. A serial multiple mediation model demonstrated that psychological safety indirectly influenced the competence of nurse educator through a sense of coherence and work engagement. Conclusions: Supportive organizational environments foster a sense of coherence, enabling effective resource utilization and the competence of nurse educator development. While structured intervention programs such as faculty development are vital, establishing supportive systems that nurture adaptable qualities and use various resources is also essential. A positive work environment can create a cycle of increasing competency through positive attitudes toward work.